Methodologies used to verify Sexual Dimorphism through human teeh. an integrative review (Research, Society and Development, 2022)
Within the scope of human identification, there are some parameters that assume great relevance, among which the determination of sex is included. The facial and dental morphological characteristics vary according to their age, gender and facial biotype, thus, the use of teeth, whether by metric or qualitative assessment, can represent a legal dental tool applicable to human identification. Thus, this integrative review investigated which methodologies are used to verify sexual dimorphism in human teeth, as well as which teeth present greater sexual dimorphism. For the selection of articles from the last 05 years, the databases of the Virtual Health Library - BVS and PubMed were used and the sample obtained consisted of 09 publications. After analyzing the articles, the results of the studies indicated that the most used methodologies were the odontometric measurement of the mesiodistal dimension (MD), the measurement of the buccolingual width (BL) and elements 13, 23, 33 and 43 presented highly consistent and statistically significant for sexual dimorphism.